Peter Jackson - Leotta, Alfio (Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2016)
"The most comprehensive academic examination of Peter Jackson's work and career"..
Keywords: Jackson, Peter, -- 1961- -- Criticism and interpretation; Jackson, Peter; PERFORMING ARTS / Film & Video / Direction & Production; REFERENCE / General